Studied controversial issues and analyze Nasr Hamid Abu Zayd thoughts contained in voice of exile: reflections on Islam - Zainol, Nur Zainatul Nadra; Abdul Majid, Latifah
Nasr Hamid Abu Zayd was a modern Muslim thinkers who is criticizing the Quran and rejecting al-Sunnah as the second source of reference in Syariah. In fact, he called for a review of the Quran and aimed to open the doors of ijtihad for syariah laws even thought that syariah had clearly described in the Quran nor al-hadith. Abu Zayd thought about Islam were shared publicly with the publication of a bibliography titled Voice of Exile: Reflections on Islam that has been written with Esther, R. The book reveal his life since childhood till he was known as a modern Muslim thinker. His thought in criticizing the Quran and Shariah was shocked the Muslim world. This article aims to identify controversial issues and analyze his thoughts contained in this book. The method used for this study is content analysis to describe Abu Zayd’s thought about Islam. Method of identifying issues was based on a fatwa Jakim 2006 on liberalism. The results showed that he thought exists in two aspects of faith and syariah which are not in line with Islamic law. The study shows that he was a liberal and idea of liberalism was disseminated through out the book. Therefore, this book is incongruous for the Muslim community in Malaysia.